Songs and stories of the Civil War - Silverman, Jerry, 1931- (Brookfield, Conn. : Twenty-First Century Books, 2002)
Provides a history of the music and lyrics of a dozen Civil War songs, describing the circumstances under which they were created and performed.
The battle cry of freedom -- The battle hymn of the republic -- Dixie's land -- Maryland, my Maryland -- Lincoln and liberty -- Weeping sad and lonely -- Tenting on the old camp ground -- When Johnny comes marching home -- Roll, Alabama, roll -- The battle of Shiloh -- Slavery chain done broke at last -- Free at last.
Includes music (piano with optional voice) to a selection of Civil War songs.
Includes bibliographical references (p. 92-93), discographies, and index.
Keywords: Music -- United States -- 19th century -- History and criticism; United States -- History -- Civil War, 1861-1865 -- Songs and music -- History and criticism -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Songs and music -- History and criticism